International Political Economy – A Modern Science (UNWE Yearbook, 2015)
This study is dedicated to a relatively young branch of political economy – the international political economy. The study’s main purpose is to clarify international political economy’s profile as an interdisciplinary social science.In historical retrospective it traces the emergence and evolution of political economy as well as its correlation to „pure“ economic theory, the economics. The wide range of the term „political economy“ under present-day conditions has been outlined; arguments have been put forward supporting the normal tendency of the resurrection of the interest in political economy from mid 20th century.The factors of social practice and the scientific and cognitive premises determining the international political economy’s recognition as an independent science with its own subject and specific methodology of research have been identified. The main theoretical doctrines developed within the framework of the international political economy have been interpreted – the external dependence theory, the hegemonic stability theory in its two versions (liberal and realistic) and the neoliberal institutionalism theory.A number of key categories of international political economy as a science have been deducted and interpreted in terms of content. The latter are examined as an abstract- theoretical reflection of real phenomena, processes and tendencies in the international economic system and analytical ideas of studying its functioning and development.Arguments have been made for the failure of the neoliberal international economic order and its theoretical foundations in the context of the global financial and economic crisis (2008 2009). The need for a new agenda for the international political economy has been justified as a wide-ranging catalogue of tasks related to the reforming of the international economic order in compliance with the economic, political and social realities of the present-day highly globalized world.